The prevalence of visual defect among commercial vehicle drivers in Selangor, Malaysia - Hoe, Victor Chee Wai (Faculty of Medicine, University of Malaya, 2006)
A cross-sectional survey of commercial vehicle drivers who were renewing their own licences was conducted at the Selangor Road Transport Department office in Padang Jawa between 1 February 2002 and 28 February 2002, using questionnaire and medical examination. The objective was to determine the prevalence of myopia, colour vision deficiency and visual field defect among the commercial vehicle drivers. The respondents that reported visual defect at the time of interview was compared with those detected by the author through medical examination. Out of the 223 respondents, 21 (9.4%) reported to have myopia by the questionnaire survey. Through the visual examination there were 63 (28.3%) with myopia (visual acuity worse than 6/12), six (2.6%) had a visual field defect and 14 (6.3%) had red-green colour deficiency. The visual defect detected during the study among the commercial vehicle drivers,which were missed at the time of the routine medical examination were significant. The process of the statutory medical examination should be reviewed.